Genetic diversity among volunteer donors of bone marrow in southeastern Brazil, according to the HLA system - Roque, Letícia Sarni; Telarolli Junior, Rodolpho; Loffredo, Leonor Castro Monteiro (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Checking the histocompatibility of the molecules of the human leukocyte antigen (HLA) system is vital for performing bone marrow transplantation with allogeneic material. The objective of this study was to characterize bone marrow donors according to gender, age, ethnicity and HLA groups at a regional hemotherapy center in Brazil. DESIGN AND SETTING: Descriptive study on registered donors at a regional hemotherapy center in a public university hospital in the southeastern region of Brazil. METHODS: The records of 66,780 donors who were registered between 2005 and June 2011 were consulted, and the variables studied were tabulated. RESULTS: There were equal numbers of male and female donors and 82.8% of them were under 45 years of age. In terms of ethnicity, 77.3% declared themselves to be white, 15.0% mixed race, 5.7% black and 2% others. In terms of immunogenetic characterization, the most frequent HLA-A allelic group was HLA-A*02, with 39.20% of the donors; in the HLA-B allelic group, the most common was HLA-B*35, with 14.18%; while in the HLA-DRB1 allelic group, the most frequent was HLA-DRB1*03, with 17.03%. Comparison between these results and data from the Brazilian Bone Marrow Donor Registry (REDOME) showed that there were demographic and immunogenetic differences due to the history of immigration in the region of Ribeirão Preto, in southeastern Brazil. CONCLUSIONS: The results reinforce the importance of understanding the demographic and immunogenic profile of regions of Brazil, in order to reduce the waiting time for a histocompatible donor.